Discovery of super–insecticide-resistant dengue mosquitoes in Asia: Threats of concomitant knockdown resistance mutations - Kasai, Shinji; Itokawa, Kentaro; Uemura, Nozomi; Takaoka, Aki; Furutani, Shogo; Maekawa, Yoshihide; Kobayashi, Daisuke; Imanishi-Kobayashi, Nozomi; Amoa-Bosompem, Michael; Murota, Katsunori; Higa, Yukiko; Kawada, Hitoshi; et al. (Science Advances, 2022)
Aedes aegypti (Linnaeus, 1762) is the main mosquito vector for dengue and other arboviral infectious diseases. Control of this important vector highly relies on the use of insecticides, especially pyrethroids. The high frequency (>78%) of the L982W substitution was detected at the target site of the pyrethroid insecticide, the voltage-gated sodium channel (Vgsc) of A. aegypti collected from Vietnam and Cambodia. Alleles having concomitant mutations L982W + F1534C and V1016G + F1534C were also confirmed in both countries, and their frequency was high (>90%) in Phnom Penh, Cambodia. Strains having these alleles exhibited substantially higher levels of pyrethroid resistance than any other field population ever reported. The L982W substitution has never been detected in any country of the Indochina Peninsula except Vietnam and Cambodia, but it may be spreading to other areas of Asia, which can cause an unprecedentedly serious threat to the control of dengue fever as well as other Aedes -borne infectious diseases. Highly insecticide-resistant mosquito vectors are an emerging threat to controlling arbovirus infectious diseases.